1995
DOI: 10.1016/0029-7844(94)00321-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Morphologic Changes of the Corpus Luteum by Transvaginal Ultrasound in Early Pregnancy Monitoring

Abstract: Our data reveal a lack of correlation between the size of the corpus luteum on ultrasound examination and known steroid products in pregnancies conceived during spontaneous cycles. Corpus luteum volume and steroid products were higher in those patients whose ovulation was induced with clomiphene citrate. Also, different morphologic appearances of the corpus luteum in early human pregnancy, based on the amount of cystic component, have no functional significance. However, a decreasing corpus luteum volume befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The corpus luteum was identified in 98% of patients in our study, higher than the 75% to 83% reported in some studies 2,4,5,8 but similar to that in 1 other report. 9 The higher rate of detection in our study compared with several prior studies may be due to the early gestational age of our study participants.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The corpus luteum was identified in 98% of patients in our study, higher than the 75% to 83% reported in some studies 2,4,5,8 but similar to that in 1 other report. 9 The higher rate of detection in our study compared with several prior studies may be due to the early gestational age of our study participants.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings with regard to sonographic features of the corpus luteum are similar to at least 1 prior study, which also found no association between the sonographic appearance of the corpus luteum and pregnancy outcome. 2 Unlike in that study, we also evaluated the RI and PSV of the corpus luteum and correlated those with first-trimester outcome. As with sonographic features, we found no association between those Doppler measurements and pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, color flow ultrasonography evaluation can also be used to detect physiological or pathological changes in the corpus luteum. Low rates of luteal blood flow were observed in non-pregnant women, while corpora lutea of pregnant women had the highest rates of blood flow (Zalud and Kurjak, 1990;Glock et al, 1995). One of the problems with color-flow imaging is that artifacts resulting from random noise during ultrasonography may resemble aberrant flow in any direction, thus obscuring true flow characteristics.…”
Section: Color-flow Doppler Ultrasonographymentioning
confidence: 99%